Analysis of Cognitive Mathematics Learning Outcomes Using the Number Head Together (NHT) Model at SMP Negeri 1 Gunungsitoli Idanoi Academic Year 2021/2022 - Wirdayanti Zebua; Amin Otoni Harefa; Yulisman Zega (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
The background of this research is based on the results of a preliminary study conducted by researchers at SMP Negeri 1 Gunungsitoli Idanoi. Problems were found, namely student learning outcomes in mathematics were still sufficient and students were less active in the learning process. The purpose of this research is to: Describe the results of learning Mathematics in the cognitive field using the Number Head Together model. This type of research is a quantitative research. The instrument used in this study was a test of student learning outcomes in the form of an essay test. The research data obtained was processed by describing the test results of the learning outcomes obtained from each student's answer sheet. The research results obtained: Based on the results of data analysis from the research that has been done, it can be concluded that: the results of learning mathematics in the cognitive field using the Number Head Together (NHT) learning model are very good categories of 46.8%, good categories of 40.7% , the adequate category is 9.4% and less is 3.1%. Overall, the results of learning Mathematics in the cognitive field of students reached the very good category, with an overall achievement of 87.5% being in the very good category.